Loneliness and self-rated physical health among gay, bisexual and other men who have sex with men in Vancouver, Canada. Issue 7 (8th April 2020) - Marziali, Megan E; Armstrong, Heather L; Closson, Kalysha; McLinden, Taylor; Wang, Lu; Barath, Justin; Harris, Marianne; Roth, Eric A; Moore, David M; Lachowsky, Nathan J; Hogg, Robert S; Sang, Jordan M; et al.
Abstract : Background: Due to stigma and discrimination, gay, bisexual and other men who have sex with men (gbMSM) potentially carry a heightened burden of loneliness. This analysis investigates loneliness among gbMSM and its relationship with self-rated physical health, along with the mediating effect of depression. Methods: Participants were recruited using respondent-driven sampling into the Momentum Health Study (February 2012–February 2015) with follow-up visits occurring every 6 months till February 2018. Using computer-assisted self-interviews, measures of loneliness were assessed using a 6-item Loneliness Scale for Emotional and Social Loneliness (lonely vs not lonely). Current physical health was self-assessed (poor, fair, good, very good or excellent). A multivariable generalised linear-mixed model with a logit link function was used to examine the relationship between loneliness and self-rated physical health. We further investigated the mediating effect of depressive symptomatology on this relationship via the Hospital Anxiety and Depression Scale. Results: Of the 770 participants included, we found that 61% (n=471) experienced loneliness at baseline. Of the 674 (88%) who reported good/very good/excellent physical health, 59% (n=391) reported loneliness, compared with 87% (n=80) of those in poor/fair self-rated physical health who reported feeling lonely. After adjustment for confounding, loneliness was associated with poor self-rated physical health (adjusted OR 1.71; 95% CI 1.13 to 2.60). Depressive symptomatology was found to partially mediate this relationship. CONCLUSION: There may be a need for the integration of social, mental and physical health programming, targeted towards gbMSM, to alleviate the degree of loneliness experienced and its co-occurrence with poor self-rated physical health.